(:unas) unassigned - Salomi Papadima-Sophocleous (My University, 2020)
EUROCALL Association Executive Committee member meetings and tasks, Coordinator of the Association nine Special Interest Groups (SIGs), Academic committee for EuroCALL Association annual conference Proceedings abstract reviewer, conference sessions chair, etc.